Corn Starch‐Chitosan Proportion Affects Biodegradable Film Performance for Food Packaging Purposes. (25th February 2021) - Bof, María Julieta; Locaso, Delia Elisa; García, María Alejandra
Abstract: This work proposes an advance towards the scaling of biodegradable films based on corn starch and chitosan, considering the relevant film properties that condition their use for food packaging and their economic feasibility. The influence of corn starch: chitosan (CS:CH) proportion and chitosan molecular weight used in the formulation is also studied. Chitosan (CH) addition improves film forming dispersions (FFDs) stability stored under refrigerated conditions and enhances the film UV barrier properties and elongation at break, however material costs are higher. Films with higher starch content exhibited higher elastic modulus and tensile strength. Water vapor barrier, heat‐sealing capacity, and sealing resistance also increase with the corn starch (CS) proportion in film formulation. Taking into consideration the chitosan type used, the polymer‐plasticiser and polymer‐solvent interactions prevail and led to the development of more flexible materials in film formulations with low molecular weight chitosan (LMW‐CH). Meanwhile, polymer‐polymer interactions also became relevant in those obtained with MMW‐CH leading to resistant films. The obtained results indicate that composite films could be used in food packaging design, with those formulated with 75% CS and 25% medium molecular weight chitosan (MMW‐CH) being a good option considering both the film's properties as well as its economical feasibility. Abstract : Composite films based on corn starch and chitosan have good potential to be used as food packaging, being those formulated with 75% CS and 25% MMW‐CH being a good option considering both the film's characteristics and the economic feasibility of its production.